Concurrent validity of a new model for estimating peak oxygen uptake based on post-exercise measurements and heart rate kinetics in swimming - Schuller, T.; Hoffmann, U.; Iglesias, X.; Chaverri, D.; Rodriguez, F. A. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
Introduction: We aimed to assess the validity of a mathematical model based on heart rate (HR) and post-exercise VOz measurements for estimating peak VO2 at the end of a swimming exercise. Its physiological rationale relies on the assumption that during the immediate recovery the systolic volume and the arterio-venous O2 difference remain practically constant for a certain period. According to Fick's principle, this leaves HR as the main parameter for changes in VO2. Method: 34 elite swimmers performed 3x200 m at increasing sub-maximal speeds, followed by a maximal 200 m swim. VO2 was measured breath-by-breath using a portable gas analyser (K4 b2, Cosmed) connected to the swimmer by a respiratory snorkel. HR was measured from RR intervals (CardioSwim, Freelap). Data were time aligned and 1-s interpolated. Exercise V02 was the average of the last 20 s during the swim [VO2(end)L and recovery VO2 was the post-exercise first 20 s average [VO2(0-20)]. The model calculates a virtual VOz at time (t) of recovery [vV02(t)t using the quotient between the peak HR during the last 10 s of the swim [HR(O)] and the 1-s interpolated value at (t) [(HR(tn multiplied by the 1-s interpolated VO2value at (t) [VO2(t)], resulting in: vVOz(t) = HR(O) I HR(t) · VO2(t). Average vV02 values were calculated for different time intervals and compared to measured exercise VO2 values (RM-ANOVA, post-hoc Tukey, *p< 0.05). Mean differences (mean~) and Pearson's coefficient of determination (R2 ) were also calculated. Results: Peak VO2 at the last 20 s during exercise (3547± SD 692 ml/min) was different from VO2(0- 20) (3431 ± 685) (mean diff. -116, 3.3%, p= 0.001). All virtual VO2 values were highly correlated with (R 2 = 0.86 to 0.96, p<O.oon and not different from VO2 (end). Best estimates (mean diff.<0.5%} were • 2 • 2 delivered by vVO2(0-20) (3564 ± 698, R = 0.96, SEE= 120) and vVO2(5-20) (3559 ± 705, R = 0.94, SEE=121). Conclusions: The difference between peak VO2 at the end of the exercise and during the immediate recovery pinpoints the inaccuracy of the 20-s recovery method of estimation and supports the need for the model. The lack of significant differences and high correlation between measured peak VO2 and estimated post-exercise vVO2 support its basic physiologica I assumption. In conclusion, the proposed mathematical model for estimating peakVO2, which couples and takes into account both HR and VO2 off-kinetics, provides valid and accurate results, while allowing the subjects to swim completely unimpeded and avoiding the uncertainty of the backward extrapolation method.